2020
DOI: 10.31234/osf.io/5zr3w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Realistic and Symbolic Threats of COVID-19 and their Unique Impacts on Wellbeing and Adherence to Public Health Behaviors

Abstract: COVID-19 threatens lives, livelihoods, and civic institutions. Although restrictive public health behaviors such as social distancing help manage its impact, these behaviors can further sever our connections to people and institutions that affirm our identities. Three studies (N=1,195) validated a brief 10-item COVID-19 threat scale that assesses 1) realistic threats to physical or financial safety, and 2) symbolic threats to one’s sociocultural identity. Studies reveal that both realistic and symbolic threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 39 publications
8
54
2
Order By: Relevance
“…Covid-19 pandemic [32,33] and can be classified as realistic threats, defined as general concerns for one's well-being [34]. While realistic threats are often related to a personal lack of control, they reflect diverse needs.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Covid-19 pandemic [32,33] and can be classified as realistic threats, defined as general concerns for one's well-being [34]. While realistic threats are often related to a personal lack of control, they reflect diverse needs.…”
Section: Plos Onementioning
confidence: 99%
“…The first need relates to the immediate risk of losing important resources (including one's life) and the second to the threat of being unable to cope with the situation (see, e.g., [31]). Research has shown that perceived threats predict attitudes (e.g., [32,35,36]), so we examined whether and how the threat of Covid-19 inspires greater support for potential surveillance technologies.…”
Section: Plos Onementioning
confidence: 99%
“…global surveillance, quarantine, isolation facilities, and control practices) in an attempt to reduce human to human transmission (WHO, 2020). The potential impacts and accompanying uncertainty of these measures are unprecedented in recent history (12). Interestingly, as individuals are generally poor predictors of their future affect (13,14), people who have yet to experience COVID-19-related countermeasures should experience the impact of these measures as less severe than people already experiencing them.…”
Section: The Effects Of Sudden Changes In External Circumstances On Mmentioning
confidence: 99%
“…global surveillance, quarantine, isolation facilities and control practices) in an attempt to reduce human-to-human transmission [ 1 ]. The potential impacts and accompanying uncertainty of these measures are unprecedented in recent history [ 14 ]. Interestingly, as individuals are generally poor predictors of their future effect ([ 15 , 16 ] but see [ 17 ]), people who have yet to experience COVID-19-related restrictions should experience the impact of these measures as less severe than people already experiencing them.…”
Section: Introductionmentioning
confidence: 99%
“…H4, self-rated mental health: Fourthly, we hypothesized that general distress will be associated with feeling of controlling the outbreak, perceived risk of COVID-19 contagion, number of protective actions taken, knowledge and worry/fear about COVID-19 [ 10 , 14 , 23 , 48 ].…”
Section: Introductionmentioning
confidence: 99%